Determinants of Liquidity Risk in the Banking System: A Systematic Literature Review - Muhammad Fikra Yafi Ulhaqqi; Mohammad Iqbal Irfany (SMART Insight, 2026)
Post-2008, managing liquidity risk—banks' ability to meet short-term obligations without major losses—has become crucial. Regulatory measures like Basel III's LCR and NSFR emerged to ensure stability. With the rise of fintech, understanding liquidity determinants is increasingly relevant for stability. This review analyzes primary determinants of liquidity risk in the banking sector, examining systematic (macroeconomic and policy-driven) and non-systematic (bank-specific) factors. It also evaluates the impact of digital banking and fintech innovations on liquidity management to inform effective risk strategies. A systematic literature review (SLR) of 30 empirical studies most relevant published from 2010 to 2024 was conducted, examining factors such as non-performing loan (financing), capital adequacy, leverage, bank size, profitability, and corporate governance. Keywords used in this study are “Liquidity and Risk” or “Management and Bank” &